Epidemiology and clinical aspect of pediatric mushroom poisonings: a 15-year retrospective analysis - Zheng, ShaoCong; Miao, Xuejiao; He, Shan (Frontiers in Pediatrics, 2025)
BackgroundMushroom poisoning is a significant public health concern, particularly in pediatric populations, where developmental differences in toxin metabolism and organ vulnerability pose unique clinical challenges. Despite its geographic and seasonal patterns, pediatric mushroom poisoning remains underrepresented in the literature, necessitating further investigation into its epidemiological and clinical characteristics.MethodsThis 15-year retrospective cohort study analyzed 73 pediatric cases (aged ≤14 years) of mushroom poisoning at a tertiary hospital in Southwest China. Epidemiological, clinical, and laboratory data were collected, and statistical analyses were performed using SPSS 26.0.ResultsEpidemiological data revealed seasonal clustering in summer and autumn, predominantly affecting older children (≥7 years). Boletus spp. accounted for most cases (71.2%), followed by Amanita (8.2%). Clinical presentations included gastrointestinal (72.6%) and neurotoxic symptoms (69.9%), with hallucinations more prevalent in non-liver injury cases (56.9% vs. 0%, p = 0.02). Severe hepatic injury, marked by elevated liver enzymes (ALT, AST, LDH) and coagulation dysfunction (APTT, PT), correlated with higher HOPE6 scores (≥3) and 100% mortality (4 deaths). The HOPE6 scoring system demonstrated prognostic utility, with a pediatric-specific threshold (≥3) predicting adverse outcomes, contrasting with adult thresholds (≥2).ConclusionsThis study highlights the critical role of hepatic injury in mortality and underscores age-dependent variations in clinical thresholds for risk stratification in pediatric mushroom poisoning. Early intensive care is advocated to improve outcomes. Future research should focus on multicenter prospective cohorts to further validate these findings and assess therapeutic interventions.